Effects of processing methods on nutritional composition and antioxidant activity of mealworm (Tenebrio molitor) larvae. Issue 6 (8th May 2019) - Baek, Minhee; Kim, Mi‐Ae; Kwon, Yun‐Suk; Hwang, Jae‐Sam; Goo, Tae‐Won; Jun, Mira; Yun, Eun‐Young
Abstract: We examined the effects of different processing methods on the nutritional composition and antioxidant activity of mealworms. After processing with nine methods, we calculated the contents of protein, fat, ash, carbohydrate, minerals (P, Ca, K, Fe, Na), vitamin B group (B1, B2, B3 ), moisture, and calories. When processed by freeze drying among freeze drying, hot air drying, oven broiling, roasting, pan frying, deep frying, boiling, steaming, and microwaving, the contents of protein, some minerals, and vitamins were the highest. The content of total minerals was lowest after deep frying, and those of vitamin B1 and B3 were the lowest after microwaving. Antioxidant activity was then evaluated using DPPH and ABTS radical scavenging assays. DPPH assays showed that microwaving, freeze drying, deep frying, steaming, boiling, and oven broiling of mealworms yielded scavenging activities of 20.9–29.0% at 2, 000 μg/mL, which was similar to the activity level (22.7–33.2%) of 40–60 μM tocopherol. ABTS assays confirmed that only freeze‐dried mealworms at 2, 000 μg/mL exhibited higher activity than 10 μM tocopherol. Interestingly, similar trends were found for antioxidant activity levels and total phenolic contents in mealworms.